2019
DOI: 10.3389/fimmu.2019.02602
|View full text |Cite
|
Sign up to set email alerts
|

Host-Microbial Interactions in Systemic Lupus Erythematosus and Periodontitis

Abstract: Background: Systemic lupus erythematosus (SLE) is a potentially fatal complex autoimmune disease, that is characterized by widespread inflammation manifesting tissue damage and comorbidities across the human body including heart, blood vessels, joints, skin, liver, kidneys, and periodontal tissues. The etiology of SLE is partially attributed to a deregulated inflammatory response to microbial dysbiosis and environmental changes. In the mouth, periodontal environment provides an optimal niche for local and syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Our findings indicate that the host environment drives changes in the oral microbiome over time. Consistently with our study on supra-gingival plaque, salivary microbial abundance was also influenced by the environment and host phenotypes 27 . While the biofilm is directly correlated to demineralization of enamel, saliva provides the source of microbes which through evolution adapted to attach to the tooth surface.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicate that the host environment drives changes in the oral microbiome over time. Consistently with our study on supra-gingival plaque, salivary microbial abundance was also influenced by the environment and host phenotypes 27 . While the biofilm is directly correlated to demineralization of enamel, saliva provides the source of microbes which through evolution adapted to attach to the tooth surface.…”
Section: Discussionsupporting
confidence: 91%
“…The 20 assayed cytokines were: MIP-1α, IL-1β, IL-4, IP-10, IL-6, IL-8, IL-10, IL-12p70, IL-13, IL-17A, IFN-γ, GM-CSF, TNF-α, MIP-1β, IFN-α, MCP-1, P-Selectin, IL-1α, sICAM-1, and E-Selectin. Following manufacturer protocols, all samples were run on a plate with 7 standards (diluted 1:4) and a control (RPMI only), with all samples, standards, and controls run in duplicate (19).…”
Section: Methodsmentioning
confidence: 99%
“…10 In addition, a recent study showed that the inflammatory response in periodontitis controls not only SLE severity, but also the magnitude of SLE disease. 11 Moreover, another clinical investigation showed that periodontal treatment appears to improve the response of SLE to immunosuppressive therapy. Therefore, further elucidation of the association between periodontitis and SLE could help to expand understanding of the aetiology of SLE and may lead to novel prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%